2010
DOI: 10.1007/s00127-010-0275-2
|View full text |Cite
|
Sign up to set email alerts
|

Economic factors and suicide rates: associations over time in four countries

Abstract: Unemployment is a major factor influencing suicide rates over long periods of time and in different national contexts. It needs to be considered as a confounding factor in evaluations of suicide prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 24 publications
2
29
1
13
Order By: Relevance
“…Por otra parte, los estudios del comportamiento suicida se han venido presentando teniendo en cuenta factores multicausales, tales como la pobreza, el desempleo (Arroyave, Burdorf, Cardona, & Avendano, 2014;Ceccherini-Nelli, & Priebe, 2011;Rehkopf, & Buka, 2006), la pérdida de seres queridos, la discusión, o la ruptura de relaciones y los problemas jurídicos o laborales (Tuesca, & Navarro, 2003), los antecedentes familiares de suicidio, así como el abuso del alcohol y los estupefacientes (Ceballos, 2004), los maltratos en la infancia y el aislamiento social (Eckersley & Dear, 2002). Determinados trastornos mentales, como la depresión y la esquizofrenia, también inluyen en un gran número de suicidios (Echeverry, Aristizábal, Barraza, Aristizábal, Martínez, & Montoya 2010;Palacio, et al 2007;Organización Panamericana de la Salud, 2010).…”
Section: Introductionunclassified
“…Por otra parte, los estudios del comportamiento suicida se han venido presentando teniendo en cuenta factores multicausales, tales como la pobreza, el desempleo (Arroyave, Burdorf, Cardona, & Avendano, 2014;Ceccherini-Nelli, & Priebe, 2011;Rehkopf, & Buka, 2006), la pérdida de seres queridos, la discusión, o la ruptura de relaciones y los problemas jurídicos o laborales (Tuesca, & Navarro, 2003), los antecedentes familiares de suicidio, así como el abuso del alcohol y los estupefacientes (Ceballos, 2004), los maltratos en la infancia y el aislamiento social (Eckersley & Dear, 2002). Determinados trastornos mentales, como la depresión y la esquizofrenia, también inluyen en un gran número de suicidios (Echeverry, Aristizábal, Barraza, Aristizábal, Martínez, & Montoya 2010;Palacio, et al 2007;Organización Panamericana de la Salud, 2010).…”
Section: Introductionunclassified
“…One study using data from 1960 to 1999 included data from 21 countries grouped into three categories according to GDP per capita; results showed notably that countries with higher income presented higher suicide rates than poorer countries [27]. Other longitudinal studies also observed this trend [28-30]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a strong link between adverse economic conditions and higher levels of suicide (Ceccherini-Nelli et al, 2011;Classen and Dunn, 2012;Zivin et al, 2011). Figure 1.6.2 shows suicide rates for a number of countries that have been hard hit by the recent economic crisis.…”
Section: Suicidementioning
confidence: 98%